Primary thermometry of a single reservoir using cyclic electron tunneling to a quantum dot. Issue 1 (December 2018) - Ahmed, Imtiaz; Chatterjee, Anasua; Barraud, Sylvain; Morton, John; Haigh, James; Gonzalez-Zalba, M.
Abstract At the nanoscale, local and accurate measurements of temperature are of particular relevance when testing quantum thermodynamical concepts or investigating novel thermal nanoelectronic devices. Here, we present a primary electron thermometer that allows probing the local temperature of a single-electron reservoir in single-electron devices. The thermometer is based on cyclic electron tunneling between a system with discrete energy levels and the reservoir. When driven at a finite rate, close to a charge degeneracy point, the system behaves like a variable capacitor whose full width at half maximum depends linearly with temperature. We demonstrate this type of thermometer using a quantum dot in a silicon nanowire transistor. We drive cyclic electron tunneling by embedding the device in a radio-frequency resonator which in turn allows reading the thermometer dispersively. Overall, the thermometer shows potential for local probing of fast heat dynamics in nanoelectronic devices and for seamless integration with silicon-based quantum circuits. Local temperature measurements are important in the study of quantum thermodynamics at the nanoscale. The authors report a sensor based on cyclic electron tunnelling between a quantum dot and single-electron reservoir which can be used to provide local and precise temperature measurements in nanoelectronic devices.